PROPERTIES OF TEAK WOOD INFECTED BY Ceratocystis fimbriata - Silva, Jackeline Eliada Cichoski da; Cruz, Ariany Mendes; Pereira, Bárbara Luísa Corradi; Oliveira, Aylson Costa; Hoffmann, Waldelaine Rodrigues (Floresta, 2021)
In Brazil, the growth of Tectona grandis (teak) plantations is accompanied by an increased incidence of Ceratocystis wilt, a fungal disease that colonizes the vascular system of such tree. The objective of this work was to evaluate the properties of teak wood infected with Ceratocystis fimbriata at different radial positions. Ten 17-year-old trees (five infected and five healthy) were collected. A disk was removed from the base of each tree to determine Janka hardness, basic density, anatomical analysis, colorimetric parameters in the CIEL*a*b* system and sodium hydroxide solubility (NaOH). There were no significant differences for radial position and health for basic density and Janka hardness of the wood, with mean values of 0.488 g.cm3 and 58.66 MPa, respectively. The deposition of dark compounds was observed inside the parenchyma cells and fibers, as well as the formation of tyloses in the sapwood. Yellow pigment was predominant in the color formation of teak wood, which was influenced by radial position, with the sapwood being lighter. Regarding C. fimbriata infection, the color change was more evident in sapwood. Conversely, the NaOH solubility was lower for the sapwood attacked by the fungus. In conclusion, the changes in teak wood infected by C. fimbriata are visual and the anatomical structures do not deteriorate.